Vernonia amygdalina leaf and antioxidant potential - Alara, Oluwaseun Ruth; Abdurahman, Nour Hamid (Elsevier, 2020)
The free radicals are reactive molecules that emanate during oxidation; this can then stimulate a chain reaction that can cause cellular damage. A lot of studies had affirmed the implications of free radicals mostly the reactive oxygen species in generating over a hundred degenerative diseases in the human being; these include cancer, acquired immunodeficiency syndrome (AIDS), diabetes, central nervous system injury, arthritis, gastritis, atherosclerosis, reperfusion, and ischemia injury of different tissues. Scientific studies have postulated that the bioactive compounds mainly from natural products can protect the body system from free radicals. Thus, this chapter focuses on the antioxidant potential of Vernonia amygdalina and its toxicology.